(untitled) (Stato, Chiese e pluralismo confessionale, 2021)
SOMMARIO: 1. Premessa - 2. L’esperienza “classica”: Atene - 3. L’esperienza “classica”: Roma - 4. Il IV secolo fra continuità e rotture. Heterodoxy and religious minorities. Late Antiquity, at the end of a long journey ABSTRACT: This paper aims to encourage some reflections on the issue of the origins of religious intolerance and on the issues related to the treatment of minorities in Greek and Roman antiquity. In particular, a significant moment in this affair, destined to have prolonged effects, is constituted by the anti-Jewish revolts in Alexandria, in the mid-first century. A.D.